“Development of Pedagogical Competencies of Physical Education Teachers in Higher Education through Competency-Based Approach and Innovative Technologies” - Musayev Otabek Qudratovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the development of pedagogical competencies of physical education teachers in higher education through a competency-based approach and innovative technologies. The study focuses on integrating theoretical knowledge, practical skills, and pedagogical reflection to enhance professional competence. The paper discusses strategies for improving teachers’ professional potential through interactive lessons, modern pedagogical technologies, and competency-based approaches, emphasizing their role in improving the quality of education and students’ physical, cognitive, and social development.